Language and Enlightenment : The Berlin debates of the eighteenth century - Lifschitz, Avi (Oxford historical monographs, 2016)
What is the role of language in human cognition? Could we attain self-consciousness and construct our civilisation without language? Such were the questions at the basis of eighteenth-century debates on the joint evolution of language, mind, and culture. 'Language and Enlightenment' highlights the importance of language in the social theory, epistemology, and aesthetics of the Enlightenment. While focusing on the Berlin Academy under Frederick the Great, Avi Lifschitz situates the Berlin debates within a larger temporal and geographical framework. He argues that awareness of the historicity and linguistic rootedness of all forms of life was a mainstream Enlightenment notion rather than a feature of the so-called 'Counter-Enlightenment'. Enlightenment authors of different persuasions investigated whether speechless human beings could have developed their language and society on their own. Such inquiries usually pondered the difficult shift from natural signs like cries and gestures to the artificial, articulate words of human language.